Experimental Analysis of Effects of Installation Alignment and Solar Insolation on Power Generation by Solar Panels - Jazayeri, Moein; Uysal, Sener; Jazayeri, Kian (IEEE, 2013)
This paper mainly focuses on the effects of variations of solar irradiance on PV panel power outputs and considers the importance of choosing the right orientation for system installations. The analyses are based on real-time measured data collected during a 6-Month period (October/2012-March/2013) in Northern Cyprus. The mentioned data presents the months with the lowest solar insolation and the results clearly illustrate the direct relationship between the amounts of the solar irradiance and power generation by PV panels. The results can be utilized for effective use of PV systems, especially for rural areas and locations with relatively less amounts of available solar irradiance.
3rd IEEE Global Humanitarian Technology Conference (GHTC) -- OCT 20-23, 2013 -- San Jose, CA
Keywords: photovoltaics; solar energy; solar insolation; solar power generation; solar data collection; sun's position in the sky